A study of the influence of glucosamine hydrochloride compounds on certain links of connective tissue metabolism and inflammatory processes in corticosteroid osteoarthrosis modelling - Osadchenko, Svitlana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
The article describes results of as biochemical study of changes in the content of articular cartilage matrix macromolecules in cartilaginous tissue, as well as markers of inflammatory processes and alkaline phosphatase activity in blood serum of rats with a model of corticosteroid dystrophy under the influence of their treatment with compounds of glucosamine hydrochloride plus glucosamine acetylsalicylate with ratios 2:1, 1:1 and 1:2 by weight and a dose of 100 mg/kg. It was found out that in ratios of 2:1 and 1:1 the above compositions produced more pronounced effects to stimulate, in the cartilage matrix, the accumulation of carbon-protein compounds, assessed by the content of hexosamines, and noncollagenous proteins, determined by the content of thyrosine. Data of biochemical studies of blood serum demonstrated reduction in the inflammatory process activity. In order to develop a new antiarthrotic drug with combined chondroprotective and anti-inflammatory effects, a composition with a ratio of 1:1 by weight is recommended.